Managerial strategies in developing healthy food product: Integrating aspect of health and food science for competitive advantage - Fitricia Grace Maria; Putri Puspita Lianti; Slamet; Yuttama Faizal Rizky; Alfizi (BIO Web of Conferences)
The rapid growth of the healthy food products market is one of main indicators of the changing trend in food and beverage industry. People nowadays aware and more selective about their health and healthy eating habit related to healthy life style. This global awareness make influence in their decision and preference of food and beverage consumptions, finally give impact in global market for healthy food products. The trend should become main focus of the food and beverage industry to make decisions about managerial strategies for the purpose of long term and competitiveness advantage. The purpose of this research is to develop an effective managerial strategy model to support the development of healthy food products regarding of the changing trend. The methods of this research using qualitative descriptive approach which examines from the articles, global data about trend and healthy food products market, and practitioners which have experiences in developing healthy food products. Results and discussions show that integration of food science and health in developing of healthy food products is a strategic step that must be taken by food companies which can be able to meet the demand of consumers to remain relevant in competitive market. Product innovation, cross-disciplinary collaboration, and marketing strategies that emphasize consumer education have also proven to provide a significant competitive advantage.